1994
DOI: 10.1182/blood.v84.9.3047.3047
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade malignant lymphoma, hepatitis C virus infection, and mixed cryoglobulinemia

Abstract: Because a close relationship has been established between mixed cryoglobulinemia and hepatitis C virus (HCV) infection, the clinical, histologic, and virologic findings of 31 patients affected by mixed cryoglobulinemia have been determined. HCV infection was investigated by the presence of anti-HCV antibodies and by polymerase chain reaction (PCR) amplification of the 52 untranslated region (52UTR), and the genotype of HCV was also determined according to Okamoto et al (J Gen Virol 73:673, 1992). A bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
53
0
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(61 citation statements)
references
References 27 publications
4
53
0
3
Order By: Relevance
“…Hepatitis C virus (HCV) causes not only chronic liver disease, but is also implicated in several lymphoproliferative disorders (Pozzato et al, 1994). The identification of CD81 as the main HCV receptor could explain this lymphotropism because this receptor is expressed in B lymphocytes (Pileri et al, 1998).…”
mentioning
confidence: 99%
“…Hepatitis C virus (HCV) causes not only chronic liver disease, but is also implicated in several lymphoproliferative disorders (Pozzato et al, 1994). The identification of CD81 as the main HCV receptor could explain this lymphotropism because this receptor is expressed in B lymphocytes (Pileri et al, 1998).…”
mentioning
confidence: 99%
“…HCV‐related cryoglobulinaemia is the most common extra‐hepatic manifestation: in three studies with 101 patients with mixed cryoglobulinaemia, up to 95% presented signs of HCV infection 5–7 . Patients with chronic hepatitis C have cryoglobulins in 36–54% of cases, 8 , 9 although most show no clinical or physical manifestations of syndromic cryoglobulinaemia.…”
Section: Mixed Cryoglobulinaemiamentioning
confidence: 99%
“…Before the association of mixed cryoglobulinaemia with HCV infection was established, prednisone and cytotoxic drugs (cyclophosphamide and chlorambucil) were often used as maintenance therapy in patients with slow progression, although with limited success 24 . Immunosuppressive therapy may present two disadvantages: possible enhancement of HCV replication and possible exacerbation of low‐grade non‐Hodgkin's lymphoma 6 ,. 24 At present, IFNα or, preferably, pegylated IFNα represent the therapy of choice for HCV‐related mixed cryoglobulinaemia, as the improved rate of sustained virological response is accompanied by a reduction in circulating cryoglobulin levels and potential clinical remission of mixed cryoglobulinaemia symptoms 7 ,.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Researchers have suggested that mixed cryoglobulinaemia may be associated with a high prevalence of low-grade NHL and that intermediate or high-grade lymphomas can also develop during the long-term follow-up in these patients. 6 In addition, the association between HCV infection and age in patients with lymphoma may reflect the cumulative risk of infection and the long interval of time that is hypothesized to elapse from the beginning of infection to clonal lymphoid proliferation. 7 We propose that while HCV may be important in the aetiology of certain subgroups of NHL, this effect may be a multifactorial process; the malignancy could be the result of interaction among one or more viral agents in combination with genetic and environmental factors.…”
mentioning
confidence: 99%